Assessment of Plasmodium falciparum PfMDR1 transport rates using Fluo‐4. Issue 9 (1st June 2014) - Friedrich, O.; Reiling, S.J.; Wunderlich, J.; Rohrbach, P.
Abstract Mutations in the multidrug resistance transporter of Plasmodium falciparum PfMDR1 have been implicated to play a significant role in the emergence of worldwide drug resistance, yet the molecular and biochemical mechanisms of this transporter are not well understood. Although it is generally accepted that drug resistance in P. falciparum is partly associated with PfMDR1 transport activity situated in the membrane of the digestive vacuole, direct estimates of the pump rate of this transport process in the natural environment of the intact host–parasite system have never been analysed. The fluorochrome Fluo‐4 is a well‐documented surrogate substrate of PfMDR1 and has been found to accumulate by actively being transported into the digestive vacuole of several parasitic strains. In the present study, we designed an approach to use Fluo‐4 fluorescence uptake as a measure of compartmental Fluo‐4 concentration accumulation in the different compartments of the host–parasite system. We performed a 'reverse Fluo‐4 imaging' approach to relate fluorescence intensity to changes in dye concentration rather than Ca2+ fluctuations and were able to calculate the overall rate of transport for PfMDR1 in Dd2 parasites. With this assay, we provide a powerful method to selectively measure the effect of PfMDR1 mutations on substrate transport kinetics. This will be of high significance for future compound screening to test for new drugs in resistant P. falciparum strains.